Deep brain stimulation: An overview of history, methods, and future developments. (December 2018) - Pycroft, Laurie; Stein, John; Aziz, Tipu
Deep brain stimulation has already revolutionised the clinical management of treatment-resistant movement disorders and offers novel treatment options for an increasing range of neurological and psychiatric illnesses. In this article, we briefly review the history of deep brain stimulation, particularly focusing on the last 50 years, which have seen rapid development in the safety and efficacy of deep brain stimulation. We then discuss the current state of the art in deep brain stimulation, focusing on emerging indications and recent technological advances that have improved the field. Finally, we consider the future developments in technology, technique, and research that will impact deep brain stimulation; particularly focusing on closed-loop stimulation techniques and emerging techniques such as optogenetics, cybersecurity risk, implantation timing, and impediments to undertaking high-quality research.